Role of receptor occupancy assays by flow cytometry in drug development. Issue 2 (16th February 2016) - Stewart, Jennifer J.; Green, Cherie L.; Jones, Nicholas; Liang, Meina; Xu, Yuanxin; Wilkins, Danice E. C.; Moulard, Maxime; Czechowska, Kamila; Lanham, David; McCloskey, Thomas W.; Ferbas, John; van der Strate, Barry. W. A.; et al.
Abstract : The measurement of the binding of a biotherapeutic to its cellular target, receptor occupancy (RO), is increasingly important in development of biologically‐based therapeutic agents. Receptor occupancy (RO) assays by flow cytometry describe the qualitative and/or quantitative assessment of the binding of a therapeutic agent to its cell surface target. Such RO assays can be as simple as measuring the number of cell surface receptors bound by an antireceptor therapeutic agent or can be designed to address more complicated scenarios such as internalization or shedding events once a receptor engages the administered therapeutic agent. Data generated from RO assays can also be used to model whether given doses of an experimental therapeutic agent and their administration schedules lead to predicted levels of receptor occupancy and whether the receptor is modulated (up or down) on cells engaged by the therapeutic agent. There are a variety of approaches that can be used when undertaking RO assays and with the ability to measure distinct subsets in heterogeneous populations, flow cytometry is ideally suited to RO measurements. This article highlights the importance of RO assays on the flow cytometric platform in the development of biotherapeutic agents. © 2016 The Authors Cytometry Part B: Clinical Cytometry Published by Wiley Periodicals, Inc.